Neutral Zone vs. Conventional Denture Fabrication: A Randomized Crossover Study on Denture Performance - Kannaiyan, Karthik; Chauhan, Arunima; Nayak, Vijayendranath; Devendaran, Riyshmaa; Peterson, Dashmita; Kanesan, Pavittra; Lakshmi, Vityaa (UI Scholars Hub, 2025)
Objectives: It is challenging to achieve satisfactory outcomes in a complete denture for patients with resorbed residual ridges. Utilization of neutral zone techniques to guide posterior denture tooth arrangement and denture base contouring has been considered for many decades. However, the evidence is still not enough to revise protocols. This study aimed to compare patient satisfaction and stability of neutral zone denture with conventional denture. Methods: A crossover clinical trial was conducted among patients with resorbed mandibular ridges. Each participant received two sets of dentures: one fabricated using the neutral zone technique and one using the conventional method, in a randomized sequence. Denture stability was assessed clinically at the time of insertion. Patient satisfaction was recorded after three weeks of wearing each denture using a structured questionnaire. Data were analyzed using paired t-tests for within-subject comparisons, and carryover effects were evaluated using pre-test. Results: The carry-over effect was not statistically significant for both satisfaction (p = 0.099) and stability (p = 0.316). The stability of neutral zone denture was significantly higher than conventional denture (p = 0.043). Conclusion: Dentures prepared using neutral zone technique have been found to be more stable when compared to ones prepared using conventional methods.